Rift valley fever virus infection among livestock handlers in Ibadan, Nigeria. Issue 6 (2nd November 2018) - Opayele, A.V.; Odaibo, G.N.; Olaleye, O.D.
ABSTRACT: Livestock handlers are occupationally exposed to Rift Valley fever virus (RVFV) because of frequent and longer contact with mosquito vectors, animal blood and other tissues. We determined the seroprevalence of RVF virus infection among livestock handlers in Ibadan, Nigeria. Blood samples were collected from 265 workers in two major livestock markets and a livestock farm. Questionnaires were administered to obtain information on risk factors that may be associated with RVF virus transmission. The blood samples were tested using enzyme-linked immunosorbent assays (ELISA) to detect multispecies anti-RVF virus IgG/IgM and human anti-RVF virus IgM. In total, 14 (5.3%) of the 265 participants tested positive for anti-RVFV IgG. Seropositive individuals were more among livestock keepers (5.6%) than butchers (3.6%). Workers that frequently visited the livestock rearing areas of the northern part of Nigeria had a statistically significant ( P  = 0.004) higher rate of infection compared to those that did not. Very few (0.8%) of these workers knew about RVF virus while none had been vaccinated against the virus infection. This study indicates that RVF virus continues to circulate sub-clinically in Nigeria, thus the need to educate and vaccinate individuals who are occupationally at risk of infection.